Construction and Performance Testing of a Fast-Assembly COVID-19 (FALCON) Emergency Ventilator in a Model of Normal and Low-Pulmonary Compliance Conditions - White, Luke A.; Mackay, Ryan P.; Solitro, Giovanni F.; Conrad, Steven A.; Alexander, J. Steven (Frontiers in Physiology, 2021)
Introduction: The COVID-19 pandemic has revealed an immense, unmet and international need for available ventilators. Both clinical and engineering groups around the globe have responded through the development of “homemade” or do-it-yourself (DIY) ventilators. Several designs have been prototyped, tested, and shared over the internet. However, many open source DIY ventilators require extensive familiarity with microcontroller programming and electronics assembly, which many healthcare providers may lack. In light of this, we designed and bench tested a low-cost, pressure-controlled mechanical ventilator that is “plug and play” by design, where no end-user microcontroller programming is required. This Fast-AssembLy COVID-Nineteen (FALCON) emergency prototype ventilator can be rapidly assembled and could be readily modified and improved upon to potentially provide a ventilatory option when no other is present, especially in low- and middle-income countries (LMICs). Hypothesis: We anticipated that a minimal component prototype ventilator could be easily assembled that could reproduce pressure/flow waveforms and tidal volumes similar to a hospital grade ventilator (Engström Carestation). Materials and Methods: We benched-tested our prototype ventilator using an artificial test lung under 36 test conditions with varying respiratory rates, peak inspiratory pressures (PIP), positive end expiratory pressures (PEEP), and artificial lung compliances. Pressure and flow waveforms were recorded, and tidal volumes calculated with prototype ventilator performance compared to a hospital-grade ventilator (Engström Carestation) under identical test conditions. Results: Pressure and flow waveforms produced by the prototype ventilator were highly similar to the Carestation. The ventilator generated consistent PIP/PEEP, with tidal volume ranges similar to the Carestation. The FALCON prototype was tested continuously for a five-day period without failure or significant changes in delivered PIP/PEEP. Conclusions: The FALCON prototype ventilator is an inexpensive and easily-assembled “plug and play” emergency ventilator design. The FALCON ventilator is currently a non-certified prototype that, following further appropriate validation and testing, might eventually be used as a life-saving emergency device in extraordinary circumstances when more sophisticated forms of ventilation are unavailable.